2015
DOI: 10.1002/adma.201405171
|View full text |Cite
|
Sign up to set email alerts
|

Low Noise, IR‐Blind Organohalide Perovskite Photodiodes for Visible Light Detection and Imaging

Abstract: Solution-processed organohalide perov-skite photodiodes that have performance metrics matching silicon, but are infrared-blind are reported. The perovskite photodiodes operate in the visible band, have low dark current and noise, high specific detectivity, large linear dynamic range, and fast temporal response. Their properties make them promising candidates for imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
253
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 288 publications
(283 citation statements)
references
References 30 publications
19
253
1
Order By: Relevance
“…65 However, the first low noise MHP photodiodes were reported in 2015 almost at the same time by four research groups, [66][67][68][69] and the reason behind this relatively long delay is important: metal halide perovskites were initially deployed in metal oxide mesoporous scaffolds, which are not suitable for photodetection due to their large capacitances. Planar junctions became more common in 2014, 70 however solution processing of these junctions was not an easy task.…”
Section: Metal Halide Perovskite Photodetectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…65 However, the first low noise MHP photodiodes were reported in 2015 almost at the same time by four research groups, [66][67][68][69] and the reason behind this relatively long delay is important: metal halide perovskites were initially deployed in metal oxide mesoporous scaffolds, which are not suitable for photodetection due to their large capacitances. Planar junctions became more common in 2014, 70 however solution processing of these junctions was not an easy task.…”
Section: Metal Halide Perovskite Photodetectorsmentioning
confidence: 99%
“…In all of these reports, D* ~10 12 Jones and EQEs of 60 to 80% in the visible were achieved. Lin et al 66 showed that the response speed in these photodiodes is RCtime limited i.e., the second term of eq. 1 dominates, obtaining a response time of 120 ns as shown by Fang et al 69 This is predominantly because of the large dielectric constant of metal halide perovskites (70 to 30 from static to 1 MHz frequencies).…”
Section: Metal Halide Perovskite Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite solar cells are not only used as energy conversion devices but can also act as photodetectors [18][19][20][21][22][23][24]. In reports by Lin et al [18], their photodetectors possessed a high detectivity beyond 10 12 Jones and a PCE of more than 12%.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of the favorable properties of methyl ammonium lead halide perovskite materials has triggered a paradigm shift in what is possible in optoelectronics. Stoichiometric wavelength tunability, low trap state density, solution-phase processability, as well as excellent light absorption and emission, make these materials well suited to applications in solar cells (12)(13)(14)(15), light-emitting diodes (16,17), photodetectors (18,19), and lasers (20)(21)(22).…”
mentioning
confidence: 99%